Metabolic syndrome in lupus patients in northeast of Iran, and their lifestyle habits - Mohammad Reza Hatef-Fard; Mina Khodabandeh; Maryam Sahebari; Majid Ghayour-Mobarhan; Zahra RezaieYazdi (Babol University of Medical Sciences, 2016)
Background: Systemic lupus erythematous is an autoimmune disease associated with atherosclerotic manifestations or metabolic disturbance due to inflammation. The aim of this study was to determine frequency of metabolic syndrome (MetS) in SLE compared to healthy controls. Methods: In this cross-sectional study, 150 SLE patients and 220 healthy volunteers were enrolled. MetS was diagnosed according to ATPIII criteria. Patients and controls were compared according to prevalence of MetS. In addition, SLE patients with and without MetS were compared according to laboratory parameters. Each patient also fulfilled a checklist about routine daily activities and diet program. Data were analyzed by SPSS-11 software. Results: MetS was significantly lower in SLE than healthy controls (18% vs 29.1%, P=0.015). Disease manifestations, major organ involvement, serum values of complements and anti-DNA antibody and pharmacological therapy did not correlate with MetS occurrence in patients. The mean TG, FBS, systolic and diastolic BP were statistically higher in lupus patients compared to healthy volunteers in contrast to waist circumference. HDL-cholesterol serum values did not show any significant difference between two groups. Conclusion: It seems that despite higher values of blood pressure, serum lipids and glucose in lupus patients, the cumulative metabolic components were in a manner to make MetS more prevalent in healthy volunteers. As far as life habits are concerned, lupus patients in general did not exercise enough and did not go on a healthy diet despite of glucocorticoid therapy and hypertension.